Modal Budaya Alumni Otomatisasi dan Tata Kelola Perkantoran (OTKP) SMKN 2 Jakarta Dalam Merespon Dunia Kerja - Arvyanti Rakhmat; Nusaibah Rohimah; Riri Anggraini (Income Journal Of Economics Development, 2026)
The high unemployment rate among graduates of Indonesian Vocational High Schools (SMK) indicates that technical competence alone is insufficient to ensure graduates' readiness to enter the world of work. This condition highlights the importance of examining social and cultural factors, particularly cultural capital, in preparing vocational graduates to respond to workplace demands. This study aims to analyze how the cultural capital of Automation and Office Governance (OTKP) alumni at SMKN 2 Jakarta is formed during the educational process and how this cultural capital plays a role in responding to the world of work. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, supported by observation and documentation, involving six OTKP alumni as the main informants and supporting informants consisting of OTKP teachers and the Special Job Exchange (BKK) of SMKN 2 Jakarta. Data validity was ensured through source triangulation, while data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The results show that alumni's cultural capital is developed through the learning process, work culture habituation, field work practice (PKL), competency certification, and collaboration between the school and the industrial world. This cultural capital is reflected in communication skills, discipline, work ethics, professionalism, practical experience, and competency certificates and diplomas. Furthermore, it supports graduates' work readiness, adaptability, and ability to respond to workplace demands, both in occupations related and unrelated to the OTKP field. This study demonstrates that vocational education plays an important role in shaping cultural capital that alumni can utilize in responding to the world of work.